Working through Boundaries - Imawan, Arga Pribadi (PCD Journal, 2022)
It is commonly assumed that multidisciplinary and interdisciplinary research collaborations involve various values, knowledge, and practices, thereby existing between science and policy. This study argues, oppositely, that multidisciplinary and interdisciplinary research collaborations are socially constructed and not to be taken for granted. To support its argument, this article uses the concept of boundary work to see how the interaction between science and policy is constructed. Taking as its case study the Ground Up consortium, a collaborative water management research programme involving the Netherlands and Indonesia, this study finds that boundary work generated and formed boundaries between science and policy through a joint call for proposal documents, research proposals, and three people operating at boundaries. Furthermore, this article shows that the collaborative research in the Ground Up consortium was a social process evidenced through three mediums: text, object, and person. This qualitative research thus uses a single-case study to explore boundary work in a consortium setting. Data were collected through a review of documents (meeting notes, research proposals, and calls for proposals) as well as in-depth interviews with three members of the Ground Up consortium.